The Effect of Profitability, Dividend Policy, and Company Value on Stock Prices - Jumiati Jumiati; Khairina Natsir (International Journal of Application on Economics and Business, 2023)
Research aims to find “empirical evidence about the effect of profitability, dividend policy, and company value on stock price of companies registered in the PEFINDO25 index of the Indonesia Stock Exchange. The population are 66 companies in the PEFINDO25 index of the Indonesia Stock Exchange during 2017 to 2020. The sample in this study are selected using purposive sampling there were 13 companies that met the criteria with 52 observational data. This research used secondary data extracted from official documentation from the Indonesia Stock Exchange website. Data analysis was carried out with panel regression model using software E-Views 9. The finding of this study indicate that profitability, dividend policy, and company affect positive and significant on stock price.